Historical Overview of Kalenderhane Mosque (4th-Century Church): Characterization of Its Frescoes Using a Multi-Analytical Approach - Ceran, İrem; Kaygısız, Ersin; Özbaş, Fatih (Romanian Inventors Forum, 2025)
This study aims to characterize the frescoes located in the basement of a historically significant building that was originally constructed as a church (Theotokos Kyriotissa) and is now functioning as a mosque (Kalenderhane). The research employs multiple analytical methods, including X-Ray Diffraction (XRD), Fourier-Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy (SEM-EDS), to investigate the material composition and preservation state of the frescoes. The results indicate significant interactions between environmental factors and the preservation state of the frescoes, highlighting the importance of ongoing conservation efforts. This study contributes to a deeper understanding of the frescoes' historical context and their significance in the architectural heritage of the site. Additionally, it provides recommendations for future research and restoration practices aimed at preserving this invaluable cultural artifact.
Keywords: Byzantine Frescoes; Pigments; Conservation; Architectural Heritage; FTIR; Raman